Efficiency of carbon sorbents in mitigating polar herbicides leaching from tropical soil - Yavari, S. (Springer Science and Business Media Deutschland GmbH, 2022)
Imidazolinones are a group of herbicides with high potential of leaching and long half-lives that are posing a threat to water resourcesâ quality especially in tropical areas. Biochar, a carbon-rich bio-sorbent, has shown its ability to stabilise organic substances in soils and therefore, potentially is able to reduce their leaching. Biochar is a sustainable and cost-effective material which can be produced from locally available wastes. This work, for the first time, evaluated the biocharâs effects on leaching of two polar members of imidazolinones family namely imazapic and imazapyr, and also OndutyÂ® which is a mixture of these two herbicides, in heavy soil of tropical paddy fields. Leaching columns accompanied with artificial irrigation were used during the laboratory experiment. The herbicides were extracted from both collected leachates and soil columns. Soil amendment with designed biochars significantly reduced the herbicidesâ leaching percentages. Oil palm empty fruit bunch (OPEFB) and rice husk (RH) were used as pyrolysis feedstock. About 16 of the applied imazapic was leached out from biochar-free soil. For RH and OPEFB biochar-amended soils, the amounts were 4.3 and 3.6, respectively. The highest percentage of imazapyr leached out from non-amended soil was (14.2) followed by RH (4.0) and OPEFB (2.8) in biochar-amended soils. Also, 15.2 of the applied OndutyÂ® was leached from non-amended soil. Adding RH and OPEFB biochars could reduce the herbicide leaching to 4.2 and 3.0, respectively. Soil amended with biochars retained the higher percentages of the herbicides in top 7.5Â cm depths. The media sorption capacities were negatively correlated to the amounts of herbicides leached out from soils but positively to the amounts of the herbicides remaining in the soil. Total amount of herbicides adsorbed by biochars-amended soils was more than 95. Cation/water bridging ion exchange, ligand exchange, electrostatic attraction, and hydrophobic partitioning are the main ways imidazolinones can be adsorbed to soil. It was concluded that biochar application has the potential to reduce polar imidazolinonesâ leaching and their environmental pollution. The custom-engineered biochars can specifically control the pesticides transfer and then can certainly enhance the biocharsâ commercial values for their applications in the environment. Graphic abstract: Figure not available: see fulltext. Â© 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH Germany, part of Springer Nature.